THE PORTRAYAL OF ANXIETY IN THEY BOTH DIE AT THE END SILVERA’S NOVEL (2017) - Felissia Nofita Susanto; Ely Nurmaily (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
This thesis goes into detail about anxiety in Adam Silvera's interesting book They Both Die at the End. Using qualitative research methods, this study looks at how anxiety is a key theme in the lives of the novel's characters and how it is woven into a complex web. The story takes place in a world where everyone knows they only have 24 hours left to live. This puts a cloud of anxiety over everything they think and do. Qualitative study methods are used to give a full picture of how anxiety is woven into the characters' lives in a complex way. The study focuses on anxiety, which is a common and complex feeling, to shed light on the character's mental and emotional turmoil. By looking at their struggles, this study hopes to show how similar they are to other people and get people to understand their deep emotional complexities. This study shows how important it is to use books to talk about anxiety, which is a common problem in modern society. By using They Both Die at the End as a way to look at anxiety, this study not only helps us understand the book better but also looks at what this feeling means in the bigger picture. Since anxiety still affects the lives of a lot of people, this study is a useful look at how it's portrayed in fiction, highlighting how important it is in our complex and emotionally charged world.Keywords: Anxiety, mental illness, novel, psychology of literature, They Both Die at The End